Evaluación del polvo de moringa (m. Oleífera) para remoción de sólidos suspendidos totales en agua residual del camal municipal de Calceta - Vera Bravo, Katherine Elizabeth (2019)
Through the present study the efficiency of the tree seed was analyzed (M. oleifera) as a coagulant substance in the treatment of wastewater from a slaughterhouse. To this end, coagulation / flocculation tests were carried out in a jar test, adding predetermined doses of the coagulant of natural origin Moringa Oleifera, which was obtained by spraying seeds and extracting their powder. The residual water sample was taken from the slaughterhouse outlet for previous treatment. In each test, 3 repetitions were made to each treatment, turbidity, color, SST were measured before and after each test, in order to calculate the removal obtained. The doses applied were (T1) 7500 mg/l, (T2) 10000 mg/l and (T3) 12000 mg/l. The results show that with an application of optimum dose of the powder (M. oleifera) of 10000 mg, it was possible to achieve a removal efficiency in color 13%, turbidity 6% and SST 41%.